Delegation skills for teachers - Knight, Jim. (London : Philadelphia : Kogan Page, 1995)
Covers : accountability, barriers to effective delegation, choosing a delegation method, choosing who to delegate to, balancing the needs of the individual with the task in hand.
Includes bibliographical references
Keywords: School management and organization; Delegation of authority